Analisis Dampak Penerapan Metode Fun Learning terhadap Motivasi Belajar dan Pembentukan Karakter Siswa - Niken Zalfitri; Relsas Yogica; Ardi Ardi; Tiara Monika; Khesya Azahra Latifa (Universitas Muhammadiyah Mataram, 2026)
Abstract: This study is a systematic literature review (SLR) with a descriptive-analytical qualitative approach that aims to comprehensively analyze the impact of applying the Fun Learning method on student learning motivation and character building. Data were obtained from 10 relevant scientific articles selected through the Google Scholar database and national journal portals. The synthesis results show that the consistent application of Fun Learning increases student learning motivation, as indicated by increased interest in learning, active participation, self-confidence, and social interaction at various levels of education. In addition, collaborative activities in Fun Learning contribute to strengthening key student character traits, particularly discipline, responsibility, cooperation, and empathy. The findings also confirm that the effectiveness of implementation is highly dependent on teachers' pedagogical competence in designing contextual, creative, and meaningful activities. Theoretically, this study reinforces the position of Fun Learning as a learning approach that integrates the affective and character domains into one innovative learning framework. Practically, the results of this study provide recommendations for teachers and schools to optimize the design of Fun Learning as an implementative strategy in increasing motivation while shaping students' character holistically in the 21st century.The Fun Learning method in the learning approach emphasizes elements of fun, creativity, and active student involvement. This study aims to analyze the impact of Fun Learning on student learning motivation and character building. A literature review shows that Fun Learning can increase student interest in learning, self-confidence, and social interaction. In addition, this approach promotes character values such as discipline, cooperation, responsibility, and empathy. However, its effectiveness is greatly influenced by the teacher's competence in designing meaningful and contextual activities. Thus, Fun Learning is a potential strategy for creating enjoyable learning and positive character development.Abstrak: Penelitian ini merupakan tinjauan literatur sistematis (SLR) dengan pendekatan kualitatif deskriptif-analitis yang bertujuan untuk menganalisis secara komprehensif dampak penerapan metode Fun Learning terhadap motivasi belajar siswa dan pembentukan karakter. Data diperoleh dari 10 artikel ilmiah relevan yang dipilih melalui basis data Google Scholar dan portal jurnal nasional. Hasil sintesis menunjukkan bahwa penerapan konsisten Fun Learning meningkatkan motivasi belajar siswa, sebagaimana ditunjukkan oleh peningkatan minat belajar, partisipasi aktif, kepercayaan diri, dan interaksi sosial di berbagai tingkatan pendidikan. Selain itu, aktivitas kolaboratif dalam Fun Learning berkontribusi pada penguatan karakter siswa, terutama disiplin, tanggung jawab, kerja sama, dan empati. Temuan ini juga menegaskan bahwa efektivitas implementasi sangat bergantung pada kompetensi pedagogis guru dalam merancang aktivitas yang kontekstual, kreatif, dan bermakna. Secara teoritis, penelitian ini memperkuat posisi Fun Learning sebagai pendekatan pembelajaran yang mengintegrasikan domain afektif dan karakter ke dalam kerangka pembelajaran inovatif. Secara praktis, hasil penelitian ini memberikan rekomendasi bagi guru dan sekolah untuk mengoptimalkan desain Fun Learning sebagai strategi implementasi dalam meningkatkan motivasi sambil membentuk karakter siswa secara holistik di abad ke-21.